Coach-reported knowledge, skills, barriers, and facilitators to including autistic athletes in CrossFit - Watkins, J. M.; Munn, E. E.; Pangelinan, M. M. (International Sport Coaching Journal, 2026)
With over 14,000 CrossFit affiliates worldwide, there is untapped potential to serve many autistic athletes. However, current CrossFit coaching certifications and continuing education programs lack autism-specific training. This study assessed CrossFit affiliates` capacity to work with autistic athletes, evaluated coach knowledge, and identified perceived barriers and facilitators to participation. Two surveys were conducted. The first, completed by 97 CrossFit affiliate owners and coaches, found that over 90% of respondents were interested in working with autistic athletes and enhancing their coaching capacity. Additionally, 59.79% indicated they had the necessary knowledge and skills to work with autistic athletes. The second survey, targeting those interested in or already working with autistic athletes (n = 20), showed that experience working with autistic athletes was positively correlated with a better understanding core characteristics of autism and related physical health issues. Consistent barriers included a lack of training/confidence, parent/athlete interest, financial support, and transportation. Facilitators included adequate coaching/support staff, behavior supports, and family/community involvement. The findings highlight a strong interest in including autistic athletes in CrossFit but also reveal significant gaps in coaches` knowledge, skills, and confidence. Addressing these gaps is crucial to increasing the capacity for autistic athletes to participate in CrossFit and other functional fitness programs.